Bisphenol A Diglycidyl Ether (BADGE) and Progesterone Do Not Induce Ca2+ Signals in Boar Sperm Cells - Rehfeld, Anders; Mendoza, Noelia; Ausejo, Raquel; Skakkebæk, Niels Erik (Frontiers in Physiology, 2020)
Aim: Exposure of boar sperm cells to Bisphenol A diglycidyl ether (BADGE) has been shown to lead to reproductive failure in sows, however, the mode of action is unknown. As we have recently shown that BADGE can interfere with Ca2+ signaling in human sperm cells through an action on CatSper, and as CatSper has been shown to be expressed in boar sperm cells, we hypothesized that a similar mechanism in the boar sperm cells could be responsible for the reproductive failure. Methods: Direct effects of BADGE and the endogenous ligand of human CatSper, progesterone, on Ca2+ signaling in human and boar sperm cells were evaluated side-by-side using a Ca2+ fluorimetric assay measuring changes in intracellular Ca2+. Effects of BADGE on Ca2+ signaling in boar sperm were furthermore assessed by flow cytometry by an independent laboratory. Results: The exact same solutions of BADGE and progesterone induced transient biphasic Ca2+ signals in human sperm cells, but failed to do so in both non-capacitated and capacitated boar sperm cells. BADGE also failed to induce transient biphasic Ca2+ signals in boar sperm cells in the flow cytometric assay. Conclusion: BADGE and progesterone failed to induce Ca2+ signals in boar sperm cells. This indicates that the signaling mechanisms leading to activation of CatSper differs between human and boar sperm cells, and suggests that the mode of action by which exposure of boar sperm cells to BADGE can lead to reproductive failure in sows does not involve effects on Ca2+ signaling.